Effect of remifentanil on consumption of sevoflurane in entropy monitored general anesthesia - Hyung Tae Kim; Hyeon Eon Heo; Young Eun Kwon; Myeong Jong Lee (Korean Journal of Anesthesiology, 2010)
BackgroundMonitoring of anesthetic depth is important for successful general anesthesia. It is well known that entropy or BIS monitoring assisted titration of anesthetic drugs decreases their consumption. This study evaluated the effect of remifentanil on consumption of sevoflurane during entropy monitored general anesthesia.MethodsPatients were randomly assigned to two groups. The R group was administered 0.1 µg/kg/min of remifentanil and inhaled sevoflurane, while the S group was administered only inhaled sevoflurane. Anesthesia was maintained using sevoflurane with nitrous oxide, and entropy was monitored. In both groups, the concentration of sevoflurane was adjusted to keep the state entropy (SE) value between 40 and 60. End-tidal sevoflurane concentration (ET), entropy value, systolic blood pressure (SBP), diastolic blood pressure (DBP) and heart rate (HR) were measured at 5 minute intervals, during a 25 minute period after intubation, skin suture and the end of surgery.ResultsET was significantly lower in the R group than the S group. There were no significant differences in entropy value between R and S groups.ConclusionsEntropy monitored titration of sevoflurane with remifentanil administration decreased ET with stable hemodynamics.